(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2023)
In Iran, the complex relation between science and law in the field of filiation is mainly in the hands of the ʿulamāʾ who are called to solve questions related to the legitimacy of children born from heterologous insemination or to discuss the concept of motherhood and surrogacy; at the same time the legislator seems unable to solve some of the doubts raised by the new technologies. While science in procreation is assisted by innovative doctrinal approaches, old questions like abortion are still accompanied by conservative solutions. The doctrine debates, whereas the statute law more often than not leaves room for doubts and uncertainty.